PD‐1‐induced proliferating T cells exhibit a distinct transcriptional signature. Issue 3 (12th July 2021) - Strazza, Marianne; Bukhari, Shoiab; Tocheva, Anna S.; Mor, Adam
Summary: Ligation of the inhibitory receptor PD‐1 on T cells results in the inhibition of numerous cellular functions. Despite the overtly inhibitory outcome of PD‐1 signalling, there are additionally a collection of functions that are activated. We have observed that CD4 + T cells stimulated through the T‐cell receptor and PD‐1 primarily do not proliferate; however, there is a population of cells that proliferates more than T‐cell receptor stimulation alone. These highly proliferating cells could potentially be associated with PD‐1‐blockade unresponsiveness in patients. In this study, we have performed RNA sequencing and found that following PD‐1 ligation proliferating and non‐proliferating T cells have distinct transcriptional signatures. Remarkably, the proliferating cells showed an enrichment of genes associated with an activated state despite PD‐1 signalling. Additionally, circulating follicular helper T cells were significantly more prevalent in the non‐proliferating population, demonstrated by enrichment of the associated genes CXCR5, CCR7, TCF7, BCL6 and PRDM1 and validated at the protein level. Translationally, we also show that there are more follicular helper T cells in patients that respond favourably to PD‐1 blockade. Overall, the presence of transcriptionally and functionally distinct T cell populations responsive to PD‐1 ligation may provide insights into the clinical differences observed following therapeutic PD‐1 blockade. Abstract : We have observed that CD4+ T cells stimulated through the T‐cell receptor and PD‐1 primarily do not proliferate; however, there is a population of cells that proliferates more than T‐cell receptor stimulation alone. In this study, we have performed RNA sequencing and found that following PD‐1 ligation the proliferating T cells showed an enrichment of genes associated with an activated state despite PD‐1 signaling. Additionally, circulating follicular helper T cells were significantly more prevalent in the non‐proliferating population, demonstrated by enrichment of the associated genes CXCR5, CCR7, TCF7, BCL6 and PRDM1 and validated at the protein level.